Regarding the issue of aquaplaning and the interaction of a car tire with the road surface through a layer of water - Frolov, A.; Leontiev, D.; Don, E.; Фролов, Андрій Анатолійович; Леонтьєв, Дмитро Миколайович; Дон, Євген Юрійович (Харківський національний автомобільно-дорожній університет, 2023)
The process of interaction of a pneumatic tire of a car wheel with the surface of the road surface, which is covered with a layer of water, affects the safety of the vehicle movement, therefore, the assessment of the effect of aquaplaning when writing the conclusions of the auto technical examination is an actual direction of research. The study of the effect of aquaplaning will allow forensic experts and specialists in the automotive industry to make an objective analysis and form non-subjective conclusions. Goal. The purpose of the work is to determine the design parameters and operational features of the pneumatic tire, as well as the speed of the vehicle on the process of interaction of the car wheel tire with the surface of the road coating, which is covered with a layer of water. Methodology. The approaches adopted in the work to solve the set goals are based on the theory of aquaplaning, the theory of the interaction of the pneumatic tire with the road surface, the theory of the vehicle and the laws of theoretical mechanics. Results. The obtained results of the research in the form of an analysis make it possible to assess the impact of the aquaplaning effect of a pneumatic tire on road safety. It was established that the thickness of the water layer affects the conditions for meeting the requirements established by the traffic rules, since the decrease in the height of the tire tread pattern leads to unstable contact of the tire with the road surface. Originality. The results of the study provided an opportunity to get an idea of the influence of the design parameters of tires on road safety in terms of forming the conclusions of the motor-technical examination. Practical value. The obtained results can be recommended to forensic experts when writing expert opinions and for expert research.
Щодо питання аквапланування та взаємодії автомобільної шини з поверхнею дорожнього покриття через шар води
Keywords: aquaplaning; car wheel; road surface; tire; adhesion utilized; adhesion ratio; аквапланування; автомобільне колесо; дорожнє покриття; шина; реалізоване зчеплення; коефіцієнт зчеплення; 629.01; 10.30977/AT.2219-8342.2023.53.0.04